Characteristics of breast cancer patients with pathological complete response after neoadjuvant chemotherapy - Kołacińska, Agnieszka; Błasińska-Morawiec, Maria; Dowgier-Witczak, Izabela; Kordek, Radzisław; Morawiec, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2010)
Objectives : Pathological complete response (pCR) after neoadjuvant systemic treatment, used in inoperable locally advanced breast cancers or resectable tumours with the intent to reduce their size, is defined as no residual cancer in the breast and axilla reported by the pathologist. Aim : The aim of the study is to characterize breast cancer patients who achieved pathological complete response after neoadjuvant systemic treatment. Material and methods : 101 consecutive patients with locally advanced breast cancer, operated on after adjuvant systemic treatment, were enrolled in the study. Results : 8.91% of patients achieved a pCR. Conclusions : The highest rate of pCR was observed in triple negative breast cancer patients, G3, with invasive ductal carcinoma, receiving a combination of anthracycline- and taxane-based chemotherapy.